More than Just Soup: Use of a Student-Led COVID-19 Social Pediatrics Initiative to Propose the Integration of Social Medicine Electives in Undergraduate Medical Education. (November 2020) - Daccache, Jennifer; Khoury, Michel; Habibi, Charlene; Bennett, Susan
Introduction: The need to educate medical students on the social forces shaping disease and health patterns is paramount in preparing incoming physicians with the aptitudes to address health inequities. Despite its well-documented merit as a model of practice, social medicine remains underrepresented at the undergraduate medical education level. We hypothesize that the success of this student-led COVID-19 initiative proposes a tangible and innovative solution to address the lack of social medicine exposure in undergraduate medical education. Methodology: We sought to evaluate the impact of sustaining clinical learning during the pandemic using the social pediatrics model as a didactic vector for clerkship students. We extracted learning objectives relevant to the teaching of social medicine from the Royal College of Physicians and Surgeons of Canada's CanMEDS framework and developed a survey aimed at evaluating the attainability of each of those objectives. The survey was distributed to students enrolled in the social pediatrics COVID-19 initiative after 6 weeks (April-May), as well as a control group. Results: Completing the survey were 19 students from the University of Ottawa Faculty of Medicine, 7 in the intervention group and 12 in the control group. Students that participated in the social pediatrics initiative yielded significantly higher values for the achievement of 6 out of 9 social medicine learning objectives when compared to the control group. Although the values followed a similar trend for the remaining 3 objectives, favoring the intervention group, they were not statistically significant. Conclusion: The positive results from this study and the COVID-19 student-led initiative template can serve as a catalyst for curricular change so as to ensure graduates are adequately trained to contend with the realities of the social landscape in which they will practice. Future plans include the incorporation of interactive social medicine experiences throughout all 4 years of medical school.